Comparison of the Colonies Number of the Germs Formed Post Operation between the Utilization of Single, Double, and Orthopedic Gloves in Closed Fracture Operations More Than 2 Hours - Deni Maulana; Yoyos Dias Ismiarto; Widya Arsa (Berkala Kedokteran, 2021)
Abstract: Post-operative infection is still one of the most common nosocomial diseases that can cause great losses because it will increase the length of stay, use of drugs, and reduce the quality of life of the patients. The risk will increase if the number of colonies is> 105 bacteria per gram of tissue. Various ways have been done to reduce the number of bacteria in the operation area, including the use of surgical gloves. This study analyzed the comparison of the level of bacterial colonies that grew on the surface of single, double, and orthopedic surgical gloves in closed fracture management for more than 2 hours at Hasan Sadikin Hospital. The statistical analysis was done with p-value = 0.011 (<0.05), which means a significant difference in the number of germ colonies that grow between single, double, and orthopedic gloves. Double gloves and orthopedic gloves have a better ability to reduce bacterial colony growth. Meanwhile, there was no significant difference in the number of bacterial colonies formed between double gloves and orthopedics. Perforation is a factor affecting the number of germ colonies that formed. The use of double gloves and orthopedic gloves in closed fracture surgery for more than 2 hours shows the number of bacterial colonies formed is less than single gloves. There was a significant difference in the rate of perforation between standard surgical gloves and orthopedic gloves. Keywords: Bacteria colony, Single glove, Double glove, Orthopaedic glove, Perforation